Evaluate the stability of synthesized allicin and its reactivity with endogenous compounds in garlic - Shanshan Zhou; Xiaoying Yan; Xuguang Qiao; Zhichang Qiu; Weihe Zhu; Xiaoming Lu; Zhenjia Zheng; Bin Zhang (npj Science of Food)
Abstract The study aimed to prepare allicin in large quantities and evaluate the effects of different conditions and endogenous substances (polyphenols and free amino acids) in garlic on its stability. The optimized synthesis conditions of allicin (DADS:HAc = 2:9, H2O2:DADS = 2:1.6, reacted for 6.5 h) were established based on response surface design. Allicin with 92.57% purity was obtained by high-speed counter-current chromatography. The results of allicin degradation experiment indicated that the degradation rate of allicin accelerated with the increases of initial concentration and temperature, the degradation process of allicin was good fit with two first-order kinetics (R2 > 0.97). The stability of allicin was higher in pH 2–5.8 than in pH 8–9. Apigenin, myricetin, and quercetin combined with peroxidase enhanced the stability of allicin. Cysteine, arginine, and histidine could react with allicin. These findings provide insights for optimizing for allicin storage and food processing applications.